An Innovative Model of Agricultural Educationand Training in Guinea: Trending Toward Self-Sustainability - Aaron J. McKim; Tyson J. Sorensen (Journal of International Agricultural and Extension Education, 2018)
Exploringlocally-designed Agricultural Education and Training (AET) programs provides opportunitiesfor the entire system of AET to improve. Recognizing this potential, researchers conducted a case study of the Centre d’Apprentissage et de Formation Professionnelle Post-Primaire (i.e.,Center for Post Primary Professional Training [CAFPPP]) located in Macenta, Guinea.The case study was completed in conjunction with a comprehensive program review and participant-engaged strategic planning process. Results illuminate CAFPPP facessignificant challenges, including (a) limited funding, (b) insufficient teacher and administrator training,(c) limited curricular scope,and (d)systematic challenges. Additionally, three critical strengthswere identified at CAFPPP,(a)utilization of an effective, practice-based educational model, (b) stakeholder support, and (c) access to fertile agricultural land. Considering bothstrengths and weaknesses, researchers and CAFPPP stakeholders co-created a model to propel CAFPPP toward itsstatedgoal of becomingan “autonomous center of excellence.”The dynamic model envisionsa school leveraging its strengths to systematically address identified weaknessesvia intersecting approaches to funding, teacher and administrator development, and graduate support. Presentation of the model is supplemented with a discussionof, and recommendationsfor, application of themodel at CAFPPP. Furthermore, opportunities for all AET programs to reflect upon, and evaluate, current strategies in light of the proposed model are discussed
Keywords: agricultural education and training; Guinea; international development; practice-based education; self-sustainability